Relação peso-comprimento das principais espécies de peixes comerciais do reservatório de tucurui (bacia do tocantins/araguaia, Brasil) - Brambilla, Eduardo Meneguzzi [UNESP]; Garcia-Ayala, James Raul [UNESP]; Travassos, Fabio Alexandre [UNESP]; Carvalho, Edmir Daniel; David, Gianmarco Silva (My University, 2015)
The Tucuruí reservoir has a great ecological and economic importance, but is lacking in basic information of population biology of fishes, especially length-weight relationship. Of the 20 species analyzed, are presented new records of the length-weight relationship for five species, one have record on gray literature and the remaining 14 have records in other studies which was compared to this study. The information generated by this work can contribute to a better environmental and fisheries management in Neotropical region, especially in Tucuruí reservoir.
Length-weight relationships of the main commercial fish species of tucuruÍ reservoir (tocantins/araguaia basin, Brazil)
Keywords: Artisanal fisheries; Dam; Population biology